THE INFLUENCE OF SMOKING HABITS ON THE DIABETIC ULCER HEALING PROCESS - Margi Rahayu, Umi; Khoirul Huda, Kholis (Journal of Applied Health Management and Technology, 2024)
Diabetic ulcers are a complication of impaired bodily function resulting from high blood glucose that occurs for a long time and is not well controlled. There is a close relationship between diabetes and an increased risk of arteriosclerosis and peripheral arterial disease. The risk increases in active smokers. Macrovascular disorders occur mainly in the infragenicular vessels (tibial and peroneal arteries). Quantitative research using cross sectional and observation on 14 grade II diabetic ulcer patients at the Kitamura Clinic Pontianak to see how smoking habits influence the wound healing process. The smoking habit is one of the main risk factors that can slow down or even inhibit the healing process of diabetic ulcers